The Cambridge companion to Marx - Carver, Terrell (Cambridge University, 2013)
In the wake of the collapse of Marxism-Leninism in Eastern Europe the question arises as to how important Marx's work is now. This volume places Marx's writings in their historical context and separates what he actually said from what others interpreted him as saying.